2001
DOI: 10.3141/1765-03
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Effects of Washington State’s Trip-Reduction Program on Traffic Volumes and Delays: Central Puget Sound Region

Abstract: Washington State requires large employers in its nine most populous counties to encourage their employees to reduce commuting vehicle trips and to monitor progress by surveying employees. The monitoring requirement yields roughly 250,000 surveys every 2 years. Analysis of the survey results for 1999 and previous years estimated that the program removed an average of 18,500 vehicles from the road during the morning peak in 1999, with 12,600 of these in the Seattle metropolitan area. Information from the surveys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In the UK, the Department for Transport (DfT, 2005) reports the results of 24 case studies of workplace travel plans carried out in 2004 that indicated reduced car use of between 10% and 25%, while the range for school travel plans is 8-15% and 7-15% in urban areas for personalised travel planning. Next, Hillsman et al (2001) Yet, while clearly attractive, in practice the travel plan has remained a marginal transport planning tool (Boot et al, 2007;Enoch and Zhang, 2008). The question is, why?…”
Section: Introductionmentioning
confidence: 99%
“…In the UK, the Department for Transport (DfT, 2005) reports the results of 24 case studies of workplace travel plans carried out in 2004 that indicated reduced car use of between 10% and 25%, while the range for school travel plans is 8-15% and 7-15% in urban areas for personalised travel planning. Next, Hillsman et al (2001) Yet, while clearly attractive, in practice the travel plan has remained a marginal transport planning tool (Boot et al, 2007;Enoch and Zhang, 2008). The question is, why?…”
Section: Introductionmentioning
confidence: 99%
“…At the site level Cairns et al (2008) report that 24 workplace travel plans, also known as site-based 'transportation demand management' in the USA or 'company mobility management' in Europe, cut car use by between 10 and 25%, while Hillsman et al (2001) found an average 6% reduction at sites in Washington State, and NTA (2010) reported an 18% reduction in car use from workplace travel plans based on data from Ireland. Meanwhile, the Northamptonshire Transport Strategy for Growth in the UK (NCC, 2007) noted that a combination of good land-use planning and a good travel plan could achieve a modal shift of up to 20% at residential developments.…”
Section: Introductionmentioning
confidence: 99%